Generation and Applications of Human Pluripotent Stem Cells Induced into Neural Lineages and Neural Tissues - Martinez, Yannick; Dubois-Dauphin, Michel; Krause, Karl-Heinz (Frontiers in Physiology, 2012)
Human pluripotent stem cells (hPSCs) represent a new and exciting field in modern medicine, now the focus of many researchers and media outlets. The hype is well-earned because of the potential of stem cells to contribute to disease modeling, drug screening, and even therapeutic approaches. In this review, we focus on neural differentiation of these cells and their biomedical applications. We compare the various cell types available and their advantages. Finally, we provide a “state-of-the-art” report about current biomedical research using differentiated hPSCs. We focus on drug and toxicity screening and on neural tissue replacement.